A-Project: a Training Program from ASID - ALAO, Maroufou Jules (My University, 2015)
The A-project concept was originally proposed by Prof Aziz Bousfiha during the first IPIC Congress in Estoril, November 2013. This one day training programme was inspired by the European J Project but has been designed to suit African needs in training African health care professionals in the diagnosis and management of primary immunodeficiency disorders. As such, a protocol that governs and guides the execution of this training programme was developed in December 2013 to guide the A-project activities. This protocol was gradually improved to meet the training needs of the majority of continent. It is now proposed 3 levels of A-project.
Keywords: PID; ASID; Africa; Training